Menopausal Vasomotor Symptoms and Risk of Incident Cardiovascular Disease Events in SWAN - Rebecca C. Thurston; Helen E. Aslanidou Vlachos; Carol A. Derby; Elizabeth A. Jackson; Maria Mori Brooks; Karen A. Matthews; Sioban Harlow; Hadine Joffe; Samar R. El Khoudary (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Cardiovascular disease (CVD) in women has unique features, including associations with reproductive factors that are incompletely understood. Vasomotor symptoms (VMS), the classic menopausal symptom, are linked to CVD risk factors and subclinical CVD. Evidence linking VMS to CVD events is limited. We tested whether frequent and/or persistent VMS were associated with increased risk for fatal and nonfatal CVD events in SWAN (Study of Women’s Health Across the Nation). Methods and Results A total of 3083 women, aged 42 to 52 years at baseline, underwent up to 16 in‐person visits over 22 years. Assessments included questionnaires on VMS frequency (0, 1–5, or ≥6 days/2 weeks), physical measures, phlebotomy, and reported CVD events (myocardial infarction, stroke, heart failure, and revascularization). A subset of events was adjudicated via medical record. Death certificates were obtained. Relationships between baseline VMS or persistent VMS over the follow‐up (proportion of visits with frequent VMS) with combined incident nonfatal and fatal CVD were tested in Cox proportional hazards models adjusted for demographics, medication use, and CVD risk factors. Participants experienced 231 CVD events over the follow‐up. Women with frequent baseline VMS had an elevated risk of subsequent CVD events (relative to no VMS; ≥6 days: hazard ratio [HR] [95% CI], 1.51 [1.05–2.17], P=0.03; 1–5 days: HR [95% CI], 1.02 [0.75–1.39], P=0.89, multivariable). Women with frequent VMS that persisted over time also had an increased CVD event risk (>33% versus ≤33% of visits: HR [95% CI], 1.77 [1.33–2.35], P<0.0001, multivariable). Conclusions Frequent and persistent VMS were associated with increased risk of later CVD events. VMS may represent a novel female‐specific CVD risk factor.